Antioxidant and Starch Hydrolase Inhibitory Activities of the ‘Paspanguwa’ Herbal Formula of Sri Lanka - Nilakshi Jayawardena (Science Faculty of Chiang Mai University, 2019)
The antioxidant and starch hydrolase inhibitory effects of the ‘paspanguwa’ herbal formulation which is commonly consumed in Sri Lanka, possessing a combination of five major herbs, was evaluated. These properties of the individual herbs were also assessed and their synergistic/antagonistic/additive effects were observed. The following herbs were obtained in dried form from the Bowatte Ayurvedic Medicinal Hall in Kandy, Sri Lanka: Coriandrum sativum (CS), Coscinium fenestratum (CF), Hedyotis corymbosa (HC), Solanum xanthocarpum (SX) and Zingiber officinale (ZO). Five grams of the powdered herb or the formulation consisting of equal weights of each herb was added to 50 mL of water at 100°C for 5 min and cooled to room temperature. The total phenolics content (TPC), Oxygen Radical Absorbance Capacity (ORAC), DPPH radical scavenging and a-amylase & a-glucosidase inhibitory activities were quantified. The TPC and ORAC values decreased in the following order: CS>HC>SX>Mixture>CF>ZO. The DPPH radical scavenging activities decreased in the following order: CF>Mixture>CS>HC>ZO>XS. Despite the high ORAC values of CS and HC, the combination did not display additive or synergistic effects. The starch hydrolase inhibitory activities decreased in the following order: Mixture>HC>CF>SX>ZO>CS. In this instance, an enhancement was observed when the herbs were combined.